A flexible test for present bias and time preferences using land-lease contracts - Pieter A. Gautier; Aico van Vuuren (Center for Economic Studies and ifo Institute (CESifo), 2011)
When agents have present bias, they discount more between now and the next period than between period t (> 1) and t + 1. How fast the future discount rate (evaluated today) decays is an empirical question. We show that the discount function can be non-parametrically identified with contracts that specify payments that take place at various points in time in the future and which are traded and priced in a competitive market. We use a unique land lease-contract data set for Amsterdam, which has the above properties, to test for present bias in a flexible way. We find no evidence for present bias in this market. Even though we allow for a general-hyperbolic specification (which has exponential discounting as a special case), our estimates converge to an exponential discount function with a corresponding discount rate (in our baseline specification) of 8 %.
Keywords: D03; 330; present bias; hyperbolic discounting; discount rate; hedonic estimation; Zeitpräferenz; Abzinsung; Bodennutzung; Immobilien-Leasing; Amsterdam